2019
DOI: 10.1002/cbin.11099
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations in amniotic fluid mesenchymal stem cells derived from normal and fetus‐affected gestations: A focus on myogenic and neural differentiations

Abstract: Amniotic fluid‐derived mesenchymal stem cells (AF‐MSCs) are autologous to the fetus and represent a potential alternative source for the regenerative medicine and treatment of perinatal disorders. To date, AF‐MSCs differentiation capacity to non‐mesodermal lineages and epigenetic regulation are still poorly characterized. The present study investigated the differentiation potential of AF‐MSCs toward neural‐like cells in comparison to the mesodermal myogenic lineage and assessed epigenetic factors involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…AF‐MSCs were differentiated into three lineages, such as adipogenic, osteogenic, and chondrogenic, to confirm their differentiation potential in vitro as described in . Adipogenic differentiation was induced using STEMPro adipogenic differentiation medium (Gibco, Thermo Fisher Scientific) for 12 days and then lipid droplets were stained using freshly diluted Oil Red O solution (3:2 ratio in distilled water).…”
Section: Methodsmentioning
confidence: 99%
“…AF‐MSCs were differentiated into three lineages, such as adipogenic, osteogenic, and chondrogenic, to confirm their differentiation potential in vitro as described in . Adipogenic differentiation was induced using STEMPro adipogenic differentiation medium (Gibco, Thermo Fisher Scientific) for 12 days and then lipid droplets were stained using freshly diluted Oil Red O solution (3:2 ratio in distilled water).…”
Section: Methodsmentioning
confidence: 99%
“…No aneuploidies were detected during clinical diagnostics in samples from both groups. hAFSCs {n = 3 samples from healthy gestations and n = 3 samples from pathological gestations concomitant with polyhydramnios ([Pat1: diagnosed with fetal gastric atony], [Pat2: diagnosed with fetal esophageal atresia], [Pat3: diagnosed with Treacher Collins syndrome])} were isolated using a two-stage protocol as described in Gasiūnienė et al (2019b) (protocol approved by the Vilnius Regional Biomedical Research Ethics Committee, No. 158200-18/7-1049-550, version No.…”
Section: Isolation Of Hafscsmentioning
confidence: 99%
“…It should also be emphasized that scientific data about hAFSCs derived from fetus-affected gestations are very limited. Our group previously showed that hAFSCs from normal and fetus-affected gestations had similar stem cell characteristics and potential to differentiate toward mesodermal (adipogenic, osteogenic, chondrogenic, and myogenic) as well as ectodermal (neurogenic) lineages (Gasiūnienė et al, 2019b;Zentelytė et al, 2020). However, no scientific data exist on the metabolic characteristics of these two types of hAFSCs, nor are there any data on the neurogenic and neurotrophic potential of hAFSCs obtained exclusively from polyhydramnios samples.…”
Section: Introductionmentioning
confidence: 99%
“…2.4 | RNA and miRNA expression analysis AF-MSCs from normal and fetus-diseased gestation were cultivated up to passage 5, then RNA was isolated for genes and miRNA expression analysis by RT-qPCR as described earlier. 20 To normalize all experimental data, as reference genes GAPDH and RNU 48 were used.…”
Section: Flow Cytometrymentioning
confidence: 99%